Treatment with IgM-enriched immunoglobulin in sepsis: a matched case-control analysis (2021)
The therapeutic potential of IgM-enriched immunoglobulin preparations (IgGAM) in sepsis remains a field of debate. The use of polyclonal immunoglobulins as adjuvant therapy (Esen & Tugrul, 2009; Kaukonen et al., 2014; Molnár et al., 2013; Taccone et al., 2009) has been shown to improve clinical outcomes in terms of mortality. This study analyze the impact of IgM-enriched IgG (IgGM) as additional immunomodulation. Patients and methods: This is a retrospective registry of 1196 patientswith severe sepsis and septic shock fromnine Intensive Care Units in Colombia, from routine clinical practice; 220 patients treated with IgGAM were registered. Fully matched comparators for severity and type of infection selected among patients non-treated with IgGAM. Mortality after 28 days was 30.5% among IgGAM-treated patients and 40.5% among matched comparators. Results: Multivariate Cox regression analysis showed IgGAM treatment to be the only variable protective from death after 28 days (hazard ratio 0.62; 0.45–0.86; p: 0.004). Results reinforce the importance of IgGAM treatment for favorable outcome after septic shock and are in line with recent published meta-analyses. This study showed that treatment with IgGM in patients with sepsis was an independent modulator of the 28-day associated witha lower mortality.